2023
DOI: 10.1039/d2mo00257d
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extracellular vesicles microRNA-208b-3p and microRNA-143-3p as novel biomarkers for sudden cardiac death prediction in acute coronary syndrome

Abstract: Acute coronary syndrome (ACS) occurs as a result of myocardial ischemia that can give rise to a variety of acute cardiovascular events, including arrhythmia, heart failure and sudden cardiac death...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This study found that the main causes of death from circulatory diseases were sudden cardiac death, acute myocardial infarction and cerebral hemorrhage. Huang S et al [27] reported in the literature that the annual incidence of sudden cardiac death in China is about 41.84 per 100,000, which is the country with the highest incidence of sudden cardiac death in the world. injury-poisoning contribute to a signi cant disease burden in society, with Mulima G et al [28] reporting that more than ve million people die from injuries each year, accounting for 9% of all deaths worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the main causes of death from circulatory diseases were sudden cardiac death, acute myocardial infarction and cerebral hemorrhage. Huang S et al [27] reported in the literature that the annual incidence of sudden cardiac death in China is about 41.84 per 100,000, which is the country with the highest incidence of sudden cardiac death in the world. injury-poisoning contribute to a signi cant disease burden in society, with Mulima G et al [28] reporting that more than ve million people die from injuries each year, accounting for 9% of all deaths worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Published role Reference miR-10a-5p Inhibits autoimmune T-cell responses [71] miR-19b-3p a) Increases innate immune response including TLR4 [72,73] miR-23b-3p Reduces cardiomyopathy by targeting/ reducing MyD88-induced NF𝜅B [74,75] miR-26a-5p Reduces fibrosis in lung, reduced in DCM patients and protects heart in animal model [76,77] miR-30a-5p Increased with CVB3 infection, protects against CVB3 myocarditis [78][79][80] miR-31-5p Targets CD40L and SAP to prevent activation of T helper cells [81] miR-99b-5p Inhibits NLRP3 inflammasome, inhibits PI3K/AKT/mTOR signaling [82,83] miR-125b-5p Associated with a number of cardiovascular diseases, but shown to inhibit IL-1𝛽 by targeting TRAF6/MAPK/NF𝜅B signaling [84][85][86][87] miR-143-3p Decreases TLR4, MyD88, and NF𝜅B and increases IL-10 [88] miR-145-5p Decreases TLR4 and PI3K/AKT/mTOR signaling [89,90] miR-148a-3p Inhibits IL-1𝛽 damaging effects and is inhibited by IL-1𝛽, inhibits NF-𝜅B during acute viral myocarditis [91,92] miR-148b-3p Increases proliferation of MSCs and Th2 responses that inhibit TLR4 [93,94] miR-152-3p Decreases PI3K/AKT signaling, inhibits mitochondrial autophagy [95,96] miR-186-5p Increases anti-viral beta-defensin-1 [97] miR-208b-3p Biomarker of sudden cardiac death, but fibroblasts treated with this miR when implanted in myocardial infarcts regenerated the heart and improved cardiac function [98,99] miR-339-5p Targets NEAT1 which regulates innate immune function [100,101] miR-345-5p Targets Drp1 and induces mitochondrial fission, decreases fibrosis by targeting HIF1a [77,102] miR-486-5p Increased with viral infections, but antiviral role…”
Section: Human Mirmentioning
confidence: 99%
“…These molecules stand out for their high stability [17]-an important criterion in the search for clinical biomarkers. In fact, the analysis of different miRNAs has been investigated as an important tool in the diagnosis, treatment and understanding of cancer [18][19][20][21], neurological disorders [22][23][24] and cardiovascular diseases [25][26][27].…”
Section: Introductionmentioning
confidence: 99%